Running Out of Time: The Impact and Value of Flexibility in On-Demand Crowdwork - Yin, Ming; Suri, Siddharth; Gray, Mary L. (The 36th ACM Conference on Human Factors in Computing Systems (CHI), 2018)
With a seemingly endless stream of tasks, on-demand labor markets appear to offer workers flexibility in when and how much they work. This research argues that platforms afford workers far less flexibility than widely believed. A large part of the “inflexibility” comes from tight deadlines imposed on tasks, leaving workers little control over their work schedules. We experimentally examined the impact of offering workers control of their time in on-demand crowdwork. We found that granting higher “in-task flexibility” dramatically affected the temporal dynamics of worker behavior and produced a larger amount of work with similar quality. In a second experiment, we measured the compensating differential and found that workers would give up significant compensation to control their time, indicating workers attach substantial value to in-task flexibility. Our results suggest that designing tasks which give workers direct control of their time within tasks benefits both buyers and sellers of on-demand crowdwork.